Chapter Risk Management to Enhance Performance in the Construction SME Sector; Theory and Case Study - Simota, Jan (InTechOpen, 2018)
Dynamic changes and increasing competition in global markets have caused changes in the management of small and medium enterprises (SMEs). Due to this fact, many SME companies try to implement different methods for strategy and operation management, quality and improvement management, risk management, etc. But the problem is the efficiency and implementation of these methods in the SME company. One way to achieve higher efficiency is the integration of management methods, meaning the combination of performance management with quality, process and risk management. This approach is also recommended in the ISO standards for quality. It was reflected in a new revision of the ISO 9001 standards in the year 2015. Performance can be described by the financial and non-financial key performance indicators (KPI), covering the cost, quality and time indicators that have been implemented in the balanced scorecard framework (BSC). The aim of this chapter is to present a methodological framework, which leads to the integration of the key performance indicators (KPI) in relation to the key risk indicators (KRI), which may affect the KPIs and overall SME performance. This framework combines a process analysis and modelling with risk and qualitative or quantitative risk assessment techniques. The case study describes its practical implementation and the verification of the designed framework. The results of this research will help to build an effective management system for performance and risk management and quality management for the business processes of SMEs.